2014
DOI: 10.1017/s0305000913000524
|View full text |Cite
|
Sign up to set email alerts
|

The role of maternal input in the development ofwh-question comprehension in autism and typical development

Abstract: Social deficits have been implicated in the language delays and deficits of children with autism (ASD); thus, the extent to which these children use language input in social contexts similarly to typically developing (TD) children is unknown. The current study investigated how caregiver input influenced the development of wh-question comprehension in TD children and language-matched preschoolers with ASD. Children were visited at four-month intervals over 1.5 years; mother-child play sessions at visits 1-2 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 53 publications
1
40
0
1
Order By: Relevance
“…Thus, their looking patterns during first half of the trial are considered to indicate their level of comprehension, and their looks away from the match later in the trial are considered to indicate noise, or boredom (Candan, Kuntay, Yeh, Cheung, Wagner & Naigles, 2012; Gertner, Eisengart& Fisher, 2006; Naigles, et al, 2011; Syrett&Lidz, 2010). Other IPL studies have found that children sometimes take longer to find the matching scene, especially with more complex/less well-learned constructions, thus demonstrating significant preferences only during the second halves of trials (Candan et al, 2012; Goodwin et al, in press; Naigles et al, 2011). We had no a priori expectations concerning whether the children in this study would show early vs. later preferences for the match, so we assessed their preferences during the first and second halves of the test trials separately, as well as the entire test trial.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…Thus, their looking patterns during first half of the trial are considered to indicate their level of comprehension, and their looks away from the match later in the trial are considered to indicate noise, or boredom (Candan, Kuntay, Yeh, Cheung, Wagner & Naigles, 2012; Gertner, Eisengart& Fisher, 2006; Naigles, et al, 2011; Syrett&Lidz, 2010). Other IPL studies have found that children sometimes take longer to find the matching scene, especially with more complex/less well-learned constructions, thus demonstrating significant preferences only during the second halves of trials (Candan et al, 2012; Goodwin et al, in press; Naigles et al, 2011). We had no a priori expectations concerning whether the children in this study would show early vs. later preferences for the match, so we assessed their preferences during the first and second halves of the test trials separately, as well as the entire test trial.…”
Section: Methodsmentioning
confidence: 86%
“…Using IPL, Naigles and her colleagues have demonstrated robust comprehension of subject-verbobject (SVO) word order by 2-year-olds with ASD (Swenson, Kelley, Fein & Naigles, 2007), and 3-year-olds with ASD were able to use the SVO frame to learn novel causative verbs (Naigles, Kelty, Jaffery, & Fein, 2011). Moreover, while the comprehension of wh-questions in children with ASD was delayed relative to TD peers, they did demonstrate reliable comprehension by age 54 months (Goodwin, Fein & Naigles, 2012; in press). Interestingly, the children's comprehension of SVO and wh-questions was evident at chronologically earlier sessions than their production of the same constructions.…”
mentioning
confidence: 89%
“…Social-pragmatic abilities might play a role in the development of wh-question understanding in both general and specific ways. In general terms, children who are more attuned to their social environment might simply pay more attention to the language their parents use, which would include wh-questions (see also Goodwin et al, 2015). In specific terms, children who are more aware of the social conventions about when and how to ask wh-questions, and who pay attention to their parents' pointing to objects when they (the parents) ask questions, would be expected to better understand the referents of wh-questions.…”
Section: Discussionmentioning
confidence: 99%
“…Two- to three-year old children first use these questions for information-seeking purposes, such as, “Where is the washcloth?” or “What are they drinking?” (Tyack and Ingram, 1977; Bloom et al, 1982; Goodwin et al, 2015), and soon also use the questions for conversational purposes like initiating or maintaining conversations, such as, “How are you?” or “What's that?” Some questions also serve a directive function, such as, “Why don't we read this one?” (James and Seebach, 1982). …”
Section: Introductionmentioning
confidence: 99%
“…Researchers who investigated these skills in children with autism utilized video modeling of conversational scripts [8], video modeling and social stories, feedback and self-management [9], pivotal response treatment, time delay procedure, script-fading procedure, and applied behavior analysis intervention conducted by a robot [10][11][12].…”
Section: Introductionmentioning
confidence: 99%